Post-Cardiac surgery patient satisfaction with quality nursing Care at Institute Jantung Negara (IJN) - Ho, Siew Eng; Gurbinder Kaur; Syed Rozaidi Wafa; Syed Zulkifli Syed Zakaria; Razali Omar (Penerbit UKM, 2006)
Quality nursing care has a great impact on patient satisfaction. Quality nursing care is perceived by the post cardiac surgery patient, as the degree of physical, emotional and spiritual needs that have to be fulfilled while hospitalisation. The objective of this study was to identify factors in quality nursing care that determine post cardiac patient satisfaction. This single cross-sectional descriptive study using ‘NURSQUAL’ instrument consisted of four elements; technical competence, information giving, assurance and empathy to measure patient satisfaction with quality nursing care. It consisted of four research questions with 33 items to measure the four elements. Between January to March 2005, 52 post cardiac surgery patients from Institute Jantung Negara (IJN), who fulfilled the inclusion criteria were recruited for this study. There was a significant difference between technical competence, information giving, assurance and empathy with patient satisfaction with p value < 0.05. The element of assurance made the strongest statistically significant unique contribution to the prediction of patient satisfaction with a p value < 0.05